Certolizumab pegol does not bind the neonatal Fc receptor (FcRn): Consequences for FcRn-mediated in vitro transcytosis and ex vivo human placental transfer. (August 2016) - Porter, Charlene; Armstrong-Fisher, Sylvia; Kopotsha, Tim; Smith, Bryan; Baker, Terry; Kevorkian, Lara; Nesbitt, Andrew
Highlights: FcRn plays a key role in active antibody transfer from mother to fetus. There was no measurable affinity of anti-TNF CZP binding to human FcRn. Human FcRn-mediated CZP transcytosis was less than the negative-control antibody. CZP transport was below detection in 5 of 6 human placentas perfused ex vivo . Our results support the hypothesis that CZP structure limits its transfer through the placenta to the fetus. Abstract: Antibodies to tumor necrosis factor (anti-TNF) are used to treat inflammatory diseases, which often affect women of childbearing age. The active transfer of these antibodies across the placenta by binding of the Fc-region to the neonatal Fc receptor (FcRn) may result in adverse fetal or neonatal effects. In contrast to other anti-TNFs, certolizumab pegol lacks an Fc-region. The objective of this study was to determine whether the structure of certolizumab pegol limits active placental transfer. Binding affinities of certolizumab pegol, infliximab, adalimumab and etanercept to human FcRn and FcRn-mediated transcytosis were determined using in vitro assays. Human placentas were perfused ex vivo to measure transfer of certolizumab pegol and positive control anti-D IgG from the maternal to fetal circulation. FcRn binding affinity (KD ) was 132 nM, 225 nM and 1500 nM for infliximab, adalimumab and etanercept, respectively. There was no measurable certolizumab pegol binding affinity, similar to that of the negative control. FcRn-mediated transcytosis across a cell layer (mean ± SD; n = 3) was 249.6 ± 25.0 (infliximab), 159.0 ± 20.2 (adalimumab) and 81.3 ± 13.1 ng/mL (etanercept). Certolizumab pegol transcytosis (3.2 ± 3.4 ng/mL) was less than the negative control antibody (5.9 ± 4.6 ng/mL). No measurable transfer of certolizumab pegol from the maternal to the fetal circulation was observed in 5 out of 6 placentas that demonstrated positive-control IgG transport in the ex vivo perfusion model. Together these results support the hypothesis that the unique structure of certolizumab pegol limits its transfer through the placenta to the fetus and may be responsible for previously reported differences in transfer of other anti-TNFs from mother to fetus.